Do Drivers of Labor Force Participation Differ for Male and Female in the Rural and Urban Labor Markets in India? - WONBIN PARK (The Journal of Indian and Asian Studies, 2024)
The labor force participation rate of women in India has decreased despite economic growth, which has limited the advancement of their rights unlike in most other countries. This paper examines the determinants of labor force participation by gender in rural and urban areas using a probit model with data from the India Human Development Survey (IHDS) for 2011–2012 to analyze the factors that restrict workforce participation. The estimation results are presented below. First, the marital status of males, both rural and urban, has a significant impact on their participation in the workforce due to family support. In contrast, females face multiple restrictions based on marital, caste and religion, demonstrating that sociocultural factors have limited their participation regardless of regional factors. Second, in rural areas, the educational years of female workers negatively affect labor participation, but the constraints of marriage are weaker than in urban areas. Women in lower castes participate more in the rural labor force, which is interpreted as a result of their livelihood in the industrial structure consisting of agriculture. On the other hand, the caste system negatively affects female participation in urban areas. Finally, these results indicate that the low-labor participation of females is the result of a complicated process influenced by various factors, including regional effects and patriarchal cultural values in India. Therefore, it is necessary to provide employment opportunities and encourage economic incentives for more women to enter the labor market spontaneously, considering regional effects in policies, in order for women to emerge as one group of social leaders.